Determination of antimicrobial and antioxidant activities of Turkish endemic Ajuga chamaepitys (L.) Schreber subsp euphratica PH Davis (Lamiaceae) - Turkoglu, S.; Turkoglu, I.; Kahyaoglu, M.; Celik, S. (Academic Journals, 2010)
In this study, the antioxidant and antimicrobial activities of methanol, water and chloroform extracts of Ajuga chamaepitys were investigated. The antioxidant properties of A. chamaepitys extracts were evaluated using different antioxidant tests, such as ABTS center dot radical scavenging capacity, DPPH center dot radical scavenging capacity, superoxide anion radical scavenging, hydrogen peroxide scavenging and metal chelating activities. These various antioxidant activities were compared with synthetic antioxidants such as butylated hydroxyanisole (BHA), butylated hydroxytoluene (BHT) and alpha-tocopherol. The water extract of A. chamaepitys exhibited the higher antioxidant capacity than that of methanol and chloroform. In addition, total phenolic compounds in the extracts of A. chamaepitys were determined as pyrocatecol equivalents. Antimicrobial activity tests were carried out using disc diffusion methods with six bacteria strains and two yeast species. The obtained results indicate that A. chamaepitys is a potential source of natural antioxidant.
Keywords: Ajuga chamaepitys; antimicrobial activity; antioxidant activity